Ketogenic diet improves fertility in patients with polycystic ovary syndrome: a brief report - Tsushima, Yumiko; Nachawi, Noura; Pantalone, Kevin M.; Griebeler, Marcio L.; Alwahab, Ula Abed (Frontiers in Nutrition, 2024)
Introduction Polycystic ovary syndrome (PCOS) affects up to 20 % of reproductive-age individuals and is strongly linked to obesity. The impacts of ketogenic diet on fertility in people with PCOS are unknown. This study aims to determine the effect of a ketogenic diet on restoration of regular menstrual cycles and fertility. Methods After approval from the Institutional Review Boards of Cleveland Clinic, a retrospective analysis was conducted using the electronic health record system. We analyzed data from thirty patients (n = 30) with polycystic ovary syndrome who followed a ketogenic diet for at least 3 months at the Cleveland Clinic, Cleveland, Ohio, USA. Main outcomes were percentage of women with restoration of regular menstrual cycles and pregnancy rate. Results All women (n = 30) had restoration of regular menstrual cycles. The overall pregnancy rate of women desiring pregnancy (n = 18) was 55.6% (n = 10). Pregnancy rate was 38.5% for women on metformin and 100% for those who were not (P = 0.036). Pregnancy rate was 62.5% for women using ovulation induction agents and 50.0% for those who did not (P = 0.66). Percent weight change between the pregnant and non-pregnant groups did not significantly differ [−8.1 ± 6.2, vs −6.4 ± 8.4, P = 0.64, respectively]. Conclusion This study reports a higher rate of pregnancy with the ketogenic diet in women with PCOS compared to existing literature.